Case Report: Compound heterozygous CEP152 c.3346-5T>C variant and chr15 deletion causing recurrent MCPH–SCKS in a Chinese pregnant woman across two consecutive pregnancies - Zhang, Tao; Yuan, Hua; Shi, Xiaoliang; He, Yao; Pan, Haitao; Zhong, Yongxing; Zhang, Jintang; Yang, Zhen; Ke, Yunyan; Chen, Yan; Zhang, Feng (Frontiers in Genetics, 2025)
BackgroundPrimary autosomal recessive microcephaly and Seckel syndrome spectrum (MCPH–SCKS) disorders are a group of autosomal recessive conditions characterized by severe growth retardation and neurodevelopmental impairment. CEP152 variants are established causes of both microcephaly and Seckel syndrome phenotypes, but the pathogenicity of different variant combinations and their clinical recurrence patterns require further verification with additional cases.MethodsClinical and genetic analyses were performed for two consecutive pregnancies of a non-consanguineous Chinese couple. Fetal phenotypes were evaluated by ultrasound and fetal MRI sequentially; copy number variation sequencing (CNV-seq) was used to detect large genomic variants, whole-exome sequencing (WES) to screen for point variants, and minigene splicing assays to characterize the functional impact of key variants.ResultsFetuses in both pregnancies were diagnosed with MCPH–SCKS and harbored identical compound heterozygous CEP152 variants: a paternally inherited splice-site variant c.3346–5T>C and a maternally inherited 129.6 kb chromosomal deletion localized to 15q21.1, encompassing the entire CEP152 gene. Minigene assays confirmed that the c.3346–5T>C variant caused aberrant splicing via intron retention and exon skipping, clarifying its pathogenicity. The second pregnancy in 2024 independently verified the pathogenicity of this variant combination and disease recurrence.ConclusionThis study represents the first report of identical compound heterozygous CEP152 variants causing MCPH–SCKS in two consecutive pregnancies. The independent occurrence in the second pregnancy not only confirms the pathogenicity of this variant combination but also provides clinical evidence for the 25% recurrence risk of autosomal recessive disorders. Furthermore, this report underscores the critical importance of comprehensive genetic testing, including CNV analysis, for the prenatal diagnosis of MCPH–SCKS, offering valuable guidance for genetic counseling and prenatal intervention in similar families.